Disturbance Observer-Based Fixed-Time Attitude Autopilot for Guided Projectile - Zhang, Hongyan; Lin, Shiyao; Wang, Yuchan; Wang, Wei (Proceedings of ... IEEE International Conference on Unmanned Systems (Online), 2023)
In this paper, a robust attitude autopilot for spinning glide guided projectile is presented. Combing with the idea of trajectory linearization control (TLC), a TLC based fixed-time converged integral sliding mode control scheme is present. Moreover, to estimate and compensate total uncertainties, a reduced-order extended state observer is developed. The stability of closed-loop system is verified via Lyapunov method. Finally, numerical simulation is carried out to demonstrate the efficiency of proposed attitude autopilot.